When Performance Trumps Gender Bias: Joint vs. Separate Evaluation - Bohnet, Iris; van Geen, Alexandra; Bazerman, Max (Management Science, 2016)
Gender bias in the evaluation of job candidates has been demonstrated in business, government, and academia, yet little is known about how to overcome it. Blind evaluation procedures have been proven to significantly increase the likelihood that women musicians are chosen for orchestras, and they are employed by a few companies. We examine a new intervention to overcome gender bias in hiring, promotion, and job assignments: an “evaluation nudge” in which people are evaluated jointly rather than separately regarding their future performance. Evaluators are more likely to base their decisions on individual performance in joint than in separate evaluation and on group stereotypes in separate than in joint evaluation, making joint evaluation the profit-maximizing evaluation procedure. Our work is inspired by findings in behavioral decision research suggesting that people make more reasoned choices when examining options jointly rather than separately and is compatible with a behavioral model of information processing. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2015.2186 . This paper was accepted by Uri Gneezy, behavioral economics.